The Pullback Asymptotic Behavior of the Solutions for 2D Nonautonomous G-Navier-Stokes Equations (Advances in Applied Mathematics and Mechanics, 2018)
The pullback asymptotic behavior of the solutions for 2D NonautonomousG-Navier-Stokes equations is studied, and the existence of its $L^2$-pullback attractors on some bounded domains with Dirichlet boundary conditionsis investigated by using the measure of noncompactness. Then the estimation ofthe fractal dimensions for the 2D G-Navier-Stokes equations is given.